The educational purpose of teaching mathematics - Abdirahmanov Abdimumin Karshi (Zien Journals, 2022)
This article is about the educational goals and objectives of teaching mathematics and provides some general concepts.
Keywords: Elements of knowledge; mastering algorithms; methodological skills.